Tarbiyah, Ta’lim, Ta’dib : Pilar Pendidikan Islam Dalam Membentuk Generasi Berkarakter - Dela Maulindah; Ahsanil ‘Azami; M Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Islam views education as a formation of human character that is obedient to Allah SWT and cotrubutes positively to society. This educational concept is based on naqliyah knowledge, which subsequently gives rise to various aqliyah knowledge. This study employ a qualitative approuch using descriptive-analytical methods to analyze several concepts of islamic education, both in term of definitions and differences. The focus of this article is to present several education concepts from an islamic perspective, specifically analyzing the concepts of Tarbiyah, Ta’lim and Ta’dib. Through these three discussions, we can derive an accurate undesrtanding of their definitions and the differences amoung these educational concepts.